2020
DOI: 10.1371/journal.pone.0243077
|View full text |Cite
|
Sign up to set email alerts
|

Gut mycobiomes are altered in people with type 2 Diabetes Mellitus and Diabetic Retinopathy

Abstract: Studies have documented dysbiosis in the gut mycobiome in people with Type 2 diabetes mellitus (T2DM). However, it is not known whether dysbiosis in the gut mycobiome of T2DM patients would be reflected in people with diabetic retinopathy (DR) and if so, is the observed mycobiome dysbiosis similar in people with T2DM and DR. Gut mycobiomes were generated from healthy controls (HC), people with T2DM and people with DR through Illumina sequencing of ITS2 region. Data were analysed using QIIME and R software. Dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 90 publications
6
63
0
Order By: Relevance
“…In fungi belonging to the phylum Basidiomycota, the cell wall is relatively thick, and the above-mentioned preliminary procedure allows for its effective destruction and facilitates the release of DNA of these fungi. Nevertheless, similar results to ours were obtained by Jayasudha et al, who employed primers for the ITS 2 region in their study and also found that Basidiomycota was the most dominant phylum in the three examined groups (control, T2D without, and T2D with diabetic retinopathy) [33]. The possibility of detecting more DNA of the phylum Basidiomycota using the ITS 2 region was indicated by Hamad et al [37], while the team of Toju, in their analyses of sets of several primers, suggested that the application of selected primers for the whole ITS region will increase the reliability of fungal species identification [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fungi belonging to the phylum Basidiomycota, the cell wall is relatively thick, and the above-mentioned preliminary procedure allows for its effective destruction and facilitates the release of DNA of these fungi. Nevertheless, similar results to ours were obtained by Jayasudha et al, who employed primers for the ITS 2 region in their study and also found that Basidiomycota was the most dominant phylum in the three examined groups (control, T2D without, and T2D with diabetic retinopathy) [33]. The possibility of detecting more DNA of the phylum Basidiomycota using the ITS 2 region was indicated by Hamad et al [37], while the team of Toju, in their analyses of sets of several primers, suggested that the application of selected primers for the whole ITS region will increase the reliability of fungal species identification [20].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were obtained by Al Bataineh et al among Emirati subjects with type 2 diabetes compared to a control group [34]. Contrary to our observations, the results by Jayasudha et al, assessing the gut mycobiome in Indian patients with type 2 diabetes, show a statistically significant difference in the alpha diversity of samples from patients with type 2 diabetes, both without and with diabetic retinopathy compared to healthy individuals [33].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it is still unclear whether differences exist in human gut microbiota between diabetic patients with and without retinopathy. Studies on gut microbial dysbiosis have identified the Bacteroidetes phylum using culture methods or have focused on mycobiome dysbiosis through Illumina sequencing of the ITS2 region ( Moubayed et al., 2019 ; Jayasudha et al., 2020 ). Therefore, this study set out to systematically detect and identify differences in gut microbial compositions of diabetic individuals with (DR) or without (DM) retinopathy and to compare each group with healthy individuals (HC) based on 16S ribosomal RNA (rRNA) gene sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are suggested to influence intestinal health and disease by suppressing the outgrowth of potential pathobionts, promoting immunoregulatory pathways, and modulating host metabolism ( Huseyin et al, 2017 ; Ni et al, 2017 ; Sam et al, 2017 ; Chin et al, 2020 ). Several clinical studies have identified a distinct fungal microbiota dysbiosis in inflammatory bowel disease (IBD), primary sclerosing cholangitis, asthma, type 2 diabetes mellitus, chronic liver diseases, Parkinson’s disease and other neurological diseases, and even colorectal cancer ( Hoarau et al, 2016 ; Sokol et al, 2017 ; Forbes et al, 2018 ; Coker et al, 2019 ; Cirstea et al, 2020 ; Jayasudha et al, 2020 ; Jiang et al, 2020 ; Lemoinne et al, 2020 ; Qiu et al, 2020 ; van Tilburg Bernardes et al, 2020 ; Ventin-Holmberg et al, 2020 ). Studies of animal models have found that commensal fungi can activate host-protective immune pathways related to epithelial barrier integrity, but can also induce reactions that contribute to events associated with IBD ( Iliev and Cadwell, 2020 ).…”
Section: Introductionmentioning
confidence: 99%